PENGARUH PERSEPSI KEADILAN PAJAK, KEWAJIBAN MORAL, DAN KEPERCAYAAN KEPADA PEMERINTAH TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Tiara Sastianing Maharani; Diana Airawaty (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to determine the influence and analysis of perceptions of tax fairness, moral obligation, and trust in the government on MSME taxpayer compliance. This study uses quantitative research. The population in this study is all MSME actors who have a Taxpayer Identification Number (NPWP) in Sedayu sub-district in 2024. The analysis technique uses SPSS. The results of the study are obtained t-values ​​for perceptions of tax fairness of 3.628 > 2.001 and a significance value of 0.001 < 0.05. It can be concluded that perceptions of tax fairness have a positive effect on MSME taxpayer compliance. Therefore, the first hypothesis (H1) is accepted. Based on the results of the hypothesis test, the t-value for moral obligation is 1.850 < 2.001 and a significance value of 0.069 > 0.05. It can be concluded that moral obligation does not affect MSME taxpayer compliance. Therefore, the second hypothesis (H2) is rejected. And, based on the results of the hypothesis test, the calculated t-value for moral obligation was -1.141 < 2.001 and a significance value of 0.259 > 0.05. It can be concluded that trust in the government has no effect on MSME taxpayer compliance. Therefore, the third hypothesis (H3) is rejected.